Peningkatan Pengetahuan Lansia Tentang Pencegahan Hipertensi Melalui Edukasi Posyandu Di Desa Polo - Mariam Mariam (Universitas Negeri Gorontalo, 2026)
Hypertension is a major non-communicable disease among older adults and may increase the risk of cardiovascular disease, stroke, kidney disorders, and reduced quality of life. This community service activity aimed to improve elderly knowledge regarding hypertension prevention through health education at the elderly Posyandu in Desa Polo. The activity involved 25 elderly participants and was conducted using direct health education, discussion, question-and-answer sessions, and evaluation through pre-test and post-test. The educational materials covered the definition of hypertension, risk factors, complications, prevention, and control. The results showed an increase in participants’ knowledge after the intervention. Before education, 21 participants (84%) were in the poor knowledge category, while only 1 participant (4%) was in the good category. After education, 20 participants (80%) reached the good category, and no participants remained in the poor category. These findings indicate that Posyandu-based health education is effective in improving elderly knowledge about hypertension prevention.